Lipid and transcriptome profile of the brain of pigs fed with different oil sources - Silva, Bruna Pereira Martins da (2022)
Pigs (Sus scrofa) are production animals of great importance for the economy due to the production of quality animal protein and for animal and human science as biomedical model animals. The brain of pigs has great similarity to that of humans and may have its fatty acid (FA) content and profile modulated by diet. Lipids act as signals that regulate several important biological processes and may influence gene expression. Thus, the study of the effects of different lipid sources on the brain transcriptome profile, is of great importance for new insights associated with animal and human health. The general aim of this study was to evaluate the effect of different sources and levels of oil on the lipid and transcriptional profile of brain tissue. The experimental diets consisted of corn and soybean meal diets containing 1.5% soybean oil (SOY1.5), or 3% soybean oil (SOY3.0), or 3% canola oil (CO), or 3% fish oil (FO). The experimental period was 98 days, the diets were offered in the growth and finishing phases of immunocastrated males, and 18 animals per treatment/diet were used. After slaughter, brain samples were collected for determination of total lipid content and for FA profiling. Total mRNA extraction was performed for the sequencing of the pig brain transcriptome. For statistical analysis of differential expression, the DESeq2 package was used, in which DEG were identified (FDR < 0.05) among brain samples. After the DEG identification, functional enrichment analysis was performed by using MetaCore software, from which metabolic pathways and networks were identified (p-value < 0.05). For the analysis of different levels of soybean oil (SOY1.5 or SOY3.0), no changes in total lipid content and FA profile were observed. The metabolic pathways and networks were associated with lipid metabolism, immune response, and calcium transport. For the analysis of the different oil sources there were no changes in total lipid content and some FA showed statistical differences. The main pathways and networks identified were associated with cell signaling, lipid metabolism, synaptic transmission, and inflammatory processes. The results found herein could guide us for a better understanding of the effects and mechanisms of dietary FA on the transcriptome and the FA profile of the brain tissue. Furthermore, these results contribute to advances in the nutrigenomics field and to improvements in animal and human health. The results allowed the writing of two manuscripts, already submitted to international scientific journals, available in chapters 1 and 2 of this dissertation.